Effects of aerosol particles on precipitation and cloud parameters over East Africa-Ethiopia using MODIS satellite data: Part 01 - Abeje Alemu, Ambachew; Raju, Jaya Prakash (Ethiopian Journal of Science and Technology, 2025)
The aerosol-cloud-precipitation interactions – ACPIs - are uncertain that show a large spatiotemporal variability in their magnitude. These things happen because of the effects of aerosol particles on precipitation and cloud parameters, environmental and meteorological conditions, industrial and agricultural influences, and other human influences and natural factors in each ecological functional area. For this study, aerosol and cloud data were retrieved from the Moderate Resolution Imaging Spectroradiometer MODIS sensors. These comprised of the aerosol optical depth AOD, Ångström exponent AET, atmospheric water vapor AWV, mean cloud fraction CFM, cloud top pressure CTP, and cloud top temperature CTT. Precipitation data is comprised of 3B43 products sourced from Tropical Rainfall Measuring Mission TRMM and the outgoing long-wave radiation OLR flux is comprised of Clouds and Earth‘s Radiant Energy System CERES satellite instruments. The study covers sixteen sites in East Africa-Ethiopia with neighboring countries - Eritrea, Djibouti, and South Sudan clustered into four regions for the periods of 2001–2022 to provide detailed information on the aerosol particles spatiotemporal effects on clouds and precipitation. The increase-decrease AWV, CFM and PPT fluctuations are with AOD opposing OLR, CTP and CTT. The parameters are oriented towards western part mostly in the southwest region of the study area. The minima values were found at the southeast cluster in 2022 for all AOD, AWV and CFM; in 2010 for PPT and OLR and in 1999 and for OLR with their maxima at northeast cluster in 2010 for AOD, AWV and CFM; in 2009 for PPT; and in 2011 and 2022 for CTP and CTT from both instruments. Accordingly, the AOD, AWV, CFM, PPT, CTP and CTT minimum values are 0.22, 1.90, 0.21, 1.15, 253.86, 504.53 and 257.73 for Terra and 0.18, 1.91, 0.27, 252.14, 533.43 and 262.94 for Aqua, and the maxima are 0.35, 2.33, 0.33, 2.26, 271.23, 619.08 and 268.49 for Terra and 0.35, 2.35, 0.41, 272.22, 640.07 and 272.58 for Aqua, respectively. The parameters OLR and AWV had the lowest optimum significant PCs at the Humera and Dahlak sites whereas the PCs retained based on AET at the Awassa site and AWV at the Dangote site were the highest. Differences in retained PCs point to different atmospheric dynamics responsible for the behavior of climate during various seasons of the year and the spatial coherence arising from both interannual and intraseasonal variability. And our observation using the HYSPLIT model and fire map confirms that transported aerosol particles in the atmosphere show varied source regions, mostly the Arabian desert and the southwest Indian ocean, at different levels.